EFEKTIVITAS MEDIA SONDAH LITERASI TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK DI KELAS XI SMAN 15 SURABAYA: Penelitian Tindakan Kelas - Meifia, Baigia Arta; Figi, Adinda Putri; Ovielia, Dilla; Dininda, Estherina Mesya; Aisiyah , Binti Nasiatul; Fitriyah , Aminatul; Prasasti , Adira Marsa Yafi; Anwar , M. Shoim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research plays a role in formulating information about the increase in student learning outcomes for Indonesian language subject matter using Sondah Literacy learning media in class XI of SMAN 15 Surabaya. The background of the research is based on the lack of interest in reading and understanding of student literacy which has an impact on the achievement of less than optimal learning outcomes. Traditional game-based learning media integrated with Indonesian language subjects in the form of Sondah Literacy was created to increase student engagement through a challenging, interesting, and enjoyable approach. Classroom Action Research (CAR) was used in this study with a duration of two cycles. Each cycle takes place with several stages, namely planning, implementation, observation, and reflection. Several types of data used in this study are the results of learning tests, student activity observation sheets, and questionnaires to determine student responses to Sondah Literacy media. The increase in student learning outcomes was seen to increase significantly in the results of the two-cycle research. Sondah Literacy media also increased student learning motivation, understanding, and participation in learning. Thus, Sondah Literacy media is proven to be effective as an innovative choice in learning Indonesian language material at the Senior High School (SMA) level.